School-Based Prevention of Bullying and Cyberbullying in Primary Education: A Systematic Review of Intervention Components and Implementation Strategies - Akhwani Akhwani; Afib Rulyansah; Jauharotur Rihlah; Nurul Aini; Fitri Mutmainnah (Academicus: Journal of Teaching and Learning, 2026)
Bullying and cyberbullying in elementary education impact students' psychological well-being, social relationships, digital safety, and learning engagement. This study aims to identify intervention components and implementation strategies for school-based bullying and cyberbullying prevention programs at the elementary education level. The study used a systematic literature review design following the PRISMA 2020 guidelines. A search was conducted in the Scopus database for English-language articles published between 2017 and 2026. Inclusion criteria included elementary school students aged 5–12 years, school-based prevention programs, reporting of implementation components or strategies, and empirical research, systematic reviews, or meta-analyses. Of the 230 initial records, 138 articles entered the eligibility stage, 9 were selected during initial screening, and 5 articles met all criteria after full-text verification. The synthesis results revealed five dominant component groups: knowledge and awareness education, socio-emotional development, bullying response skills, digital safety, and experiential learning. The most consistent implementation strategies included program integration within school hours, implementing training, using structured materials, active teacher or facilitator involvement, interactive activities, and process monitoring. Interventions more consistently improve knowledge, awareness, attitudes, program acceptance, and social-emotional competencies than directly reducing bullying and cyberbullying behaviors. This study confirms that promising programs are multicomponent, developmentally appropriate, involve the school ecosystem, and integrate offline and online bullying prevention.